2015
DOI: 10.1185/03007995.2015.1103215
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management of patients with diabetic peripheral neuropathy with L-methylfolate-methylcobalamin-pyridoxal-5-phosphate: results of a real-world patient experience trial

Abstract: In a real-world clinical setting, patients with diabetic peripheral neuropathy treated with LMF-MC-PP achieved significant improvements in total symptom score (NTSS-6) and in quality of life and functioning, together with greater medication satisfaction. A limitation of this study was the use of a survey instrument to collect data on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30% ( n = 21) of the studies were conducted in the USA , with five undertaken in Australia , four conducted in each of Germany , Japan and Spain , and three conducted in each of Denmark , Finland , Sweden , Iran and the Netherlands . Of the included studies, 47 were randomised controlled trials (RCT) , eight were nonrandomised trials , nine were pre–post studies , six were randomised cross‐over trials and one a longitudinal study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations are spontaneous burning or lightning -like pain in lower abdomen, end of lower limbs, and lateral part of thigh. During onset, it will cause great pain, it is difficult to tolerate [3,4]. Therefore, finding DNP effective method can not only relieve pain of patients, also has an important significance in reducing disability and death rate induced by diabetes.…”
Section: Introductionmentioning
confidence: 99%